A Study of specific absorption rate in human head due to electromagnetic exposure to 4G signals - Siti Rokiah Abdul Mutalik; Mohd Hafizuddin Mat; Muzammil Jusoh; A. W. N. Husna (Institute of Advanced Engineering and Science, 2019)
This paper presents a numerical analysis of the specific absorption rate in SAM phantom exposed to electromagnetic field. A two set dipole antenna operating with 1800MHz and 2600MHz were placed parallel to the z-axis and rotated in clockwise from 0o (vertical) to 180o in steps of 30o to investigate the effect of frequency and polarization. The maximum average of 1gram and 10gram of tissue have been presented to show the effect of SAR in SAM phantom model. A comparison of the mass average SAR in head shows the 1g of SAR at 2600MHz is double to 1800MHz frequency. While for 10g of SAR, slightly different for both 1800MHz and 2600MHz.